Multiple metastasized extramammary Paget's disease cured with bisphosphonate risedronate sodium after CyberKnife radiosurgery and docetaxel chemotherapy - Taku Fujimura; Sadanori Furudate; Yumi Kambayashi; Aya Kakizaki; Takahiro Haga; Akira Hashimoto; Setsuya Aiba (Wolters Kluwer Medknow Publications, 2016)
Invasive extramammary Paget's disease (EMPD) is highly metastatic to lymph nodes and other organs, including bone, and when metastatic lesions have expanded beyond the inguinal lymph node, it is difficult to cure. In this report, we present a case of multiple metastasized, receptor activator of nuclear factor kappa-B ligand-expressing EMPD in the pelvic lymph nodes successfully cured with continuous administration of bisphosphonate risedronate sodium after intensive CyberKnife radiotherapy and docetaxel monochemotherapy. Our present case suggested the usefulness of bisphosphonates as a maintenance therapy for metastatic invasive EMPD after the intensive chemoradiotherapy.